Surgical Site Infections in Pediatric Spine Surgery: Comparative Microbiology of Patients with Idiopathic and Nonidiopathic Etiologies of Spine Deformity. Issue 1 (January 2016) - Maesani, Matthieu; Doit, Catherine; Lorrot, Mathie; Vitoux, Christine; Hilly, Julie; Michelet, Daphné; Vidal, Christophe; Julien-Marsollier, Florence; Ilharreborde, Brice; Mazda, Keyvan; Bonacorsi, Stéphane; Dahmani, Souhayl
Abstract : Background: Surgical site infections (SSIs) are a concern in pediatric spine surgery with unusually high rates for a clean surgery and especially for patients with deformity of nonidiopathic etiology. Microbiologic differences between etiologies of spine deformities have been poorly investigated. Methods: We reviewed all cases of SSI in spinal surgery between 2007 and 2011. Characteristics of cases and of bacteria according to the etiology of the spine disease were investigated. Results: Of 496 surgeries, we identified 51 SSIs (10.3%) in 49 patients. Staphylococcus aureus was the most frequent pathogen whatever the etiology (n = 31, 61% of infection cases). The second most frequent pathogens vary according to the etiology of the spine deformity. It was Gram-negative bacilli (GNB) in nonidiopathic cases (n = 19, 45% of cases) and anaerobe in idiopathic cases (n = 8, 38% of cases), particularly Gram-positive anaerobic cocci (n = 5, 24% of cases). Infection rate was 6.8% in cases with idiopathic spine disease (n = 21) and 15.9% in cases with nonidiopathic spine disease (n = 30). Nonidiopathic cases were more frequently male with lower weight. American Society of Anesthesiologists score was more often greater than 2, they had more frequently sacral implants and postoperative intensive care unit stay. GNB were significantly associated with a nonidiopathic etiology, low weight, younger age and sacral fusion. SSIs were polymicrobial in 31% of cases with a mean of 1.4 species per infection cases. Conclusion: S. aureus is the first cause of SSI in pediatric spine surgery. However, Gram-positive anaerobic cocci should be taken into account in idiopathic patients and GNB in nonidiopathic patients when considering antibiotic prophylaxis and curative treatment. Abstract : Supplemental Digital Content is available in the text.